Vitamin D: An Examination of Physician and Patient Management of Health and Uncertainty. (March 2014) - Bennett, Keisa; Frisby, Brandi N.; Young, Laura E.; Murray, Deborah
Vitamin D has been a topic of much research interest and controversy, and evidence is mixed concerning its preventive effects and health benefits. The purpose of our study was to explore the decision-making strategies used by both primary care providers and community members surrounding vitamin D in relation to uncertainty management theory. We conducted semistructured interviews with primary care providers ( n = 7) and focus groups with community members ( n = 89), and transcribed and coded using the constant comparative method. Themes for providers included awareness, uncertainty, patient role, responsibility, skepticism, uncertainty management, and evolving perceptions. Community member focus group themes included uncertainty, information sources, awareness/knowledge, barriers, and patient–provider relationship. Both providers and community members expressed uncertainty about vitamin D but used conflicting strategies to manage uncertainty. Awareness of this disconnect might facilitate improved patient–provider communication.